Attitudes of Acehnese People towards Acehnese Proverbs in Relation to Education - Chairina Nasir (Studies in English Language and Education, 2015)
This study is aimed at describing proverbs from the Acehnese society and explaining the attitudes of people towards those proverbs in relation to education. The methodology applied was ethnographic using a questionnaire to obtain data. A number of 14 respondents who varied across ages, educational background and occupations participated in this study. These respondents included three housewives, two university students, one fresh graduate, one junior high school and two senior high school students, one trader, two senior citizens, one teacher and one civil servant. Based on the findings, the attitude nowadays of the Acehnese has changed radically. Out of eight adults, only three were actively using proverbs in their daily lives and teaching their children those proverbs. All of the young people, who ranged from fourteen to twenty three years old, did not use proverbs. In relation to education, proverbs are used to teach the society about courtesy, advices (e.g. for choosing companions and friends in life, child rearing, socializing/conversing, and not to mind other people’s business), and shyness as part of faith. Furthermore, a significant language shift has occurred in Aceh which has impacted Acehnese oral literature whereby more parents today prefer Indonesian to be taught as their children’s first language (Alamsyah, et al., 2011). Consequently this has put the Acehnese proverbs under the threat of becoming extinct in their own society.